Traditional theater Mendu of West Kalimantan as a Medium for Public Education - Gunta Wirawan; Herman J. Waluyo; Sarwiji Suwandi; Sahid Teguh Widodo (JP-BSI (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2020)
Traditional theater has various functions in society, a part from being an entertainment also as an education media, an explication, communication, social integration, aesthetic expression, and artistic expression. Even in the early days of its appearrance, traditional theater mendu  performances were precisely as a religious facilities. Therefore, it can be said that traditional performances are able to become archives for storing the noble values of local wisdom. This research aims to describe the function of the traditional theater mendu of West Kalimantan especially as an educational medium for the supporting community. This function could be in the form of scenes or dialogs during the show, either to the form of advices, religion advices, or inserted in jokes played by Khadam (Adam) and Mak Miskin from the common people. For the people of West Kalimantan, especially Mempawah district which is undergoing transition to modern society, the function of the performing arts should  still be very dominant in influencing the community. Therefore, the traditional theater of mendu deserves to be maintained from the threat of extinction.